Fatty Acid Conjugation Enhances the Activities of Antimicrobial Peptides - Li, Zhining; Yuan, Penghui; Xing, Meng; He, Zhumei; Dong, Chuanfu; Cao, Yongchang; Liu, Qiuyun (Recent Patents on Food, Nutrition & Agriculture, 2013)
Antimicrobial peptides are small molecules that play a crucial role in innate immunity in multi-cellular organisms, and usually expressed and secreted constantly at basal levels to prevent infection, but local production can be augmented upon an infection. The clock is ticking as rising antibiotic abuse has led to the emergence of many drug resistance bacteria. Due to their broad spectrum antibiotic and antifungal activities as well as anti-viral and anti-tumor activities, efforts are being made to develop antimicrobial peptides into future microbial agents. This article describes some of the recent patents on antimicrobial peptides with fatty acid conjugation. Potency and selectivity of antimicrobial peptide can be modulated with fatty acid tails of variable length. Interaction between membranes and antimicrobial peptides was affected by fatty acid conjugation. At concentrations above the critical miscelle concentration (CMC), propensity of solution selfassembly hampered binding of the peptide to cell membranes. Overall, fatty acid conjugation has enhanced the activities of antimicrobial peptides, and occasionally it rendered inactive antimicrobial peptides to be bioactive. Antimicrobial peptides can not only be used as medicine but also as food additives.
Keywords: self-assembly